Exploring Protective Factors for Resilience among Teachers in Islamic Elementary Schools in Remote Area - Esa Nur Wahyuni; Ali Maksum; Hidayat Ma'ruf (Journal of Innovation in Educational and Cultural Research, 2024)
Teachers in private Islamic elementary schools in remote areas of Indonesia play a crucial role in the country’s education system, showing remarkable resilience despite the challenges posed by their locations. This study explores the factors contributing to their resilience and its impact on teaching effectiveness. Using qualitative methods, data from ten teachers were gathered through in-depth interviews and observations. The study identified three key factors: socially, teachers gain resilience from their respected status in the community, their responsibility as role models, and maintaining a strong sense of responsibility to their religious leaders and alma mater; spiritually, they view their profession as a noble, Allah-blessed calling and an act of worship; and psychologically, positive emotions such as happiness, peace, and job satisfaction strengthen their resilience. Teachers’ emotional resilience is seen in their enthusiasm, sincerity, and patience despite limitations and low well-being. The study emphasizes the importance of resilience in enabling these teachers to fulfill their responsibilities and suggests strengthening these resilience factors to support them in their essential roles. Further research could extend these findings to another educational context.